Development of high antioxidant / high fiber functional peach nectar containing lutein/lycopene and various dietary fibers using D-optimal mixture design optimization - Masumeh Takalloo; Babak Ghanbarzadeh; Mostafa Soltani; Pasquale M. Falcone (Applied Food Research, 2025)
For developing a type of healthy and functional drink with high fiber and antioxidant properties, three types of dietary fiber (bamboo fiber, citrus fiber, and polydextrose) and two types of carotenoids (lycopene and lutein) were used in the peach nectar-based formulations. Based on the D-optimal mixture design, the ratio of fibers in a constant amount of fiber mixture (6 g) and the ratio of carotenoids in a constant amount of carotenoid mixture (6 mg) were selected as independent variables. 24 formulations were presented by Design Expert software, and based on anti-oxidant and physical stability tests, the highest desirability was achieved by the formulation with 100% polydextrose and 100% lycopene (F8 sample) with a desirability of 0.997. This formulation showed 88% of stability and 85% of DPPH antioxidant activity. In addition to the F8 sample, five other samples were selected for further experiments. These formulations showed total phenolic contents ranging from 85.2 to 123.6 mg GAE/100 ml, total flavonoids from 7.3 to 18.4 mg QE/ 100 ml, and vitamin C content between 9.2 and 15.8 mg/ 100 ml. The retention of lycopene and lutein after 8 weeks of storage at 4 °C ranged from 41.2-68.9% and 45.6-74.3 %, respectively. The first-order kinetic model best described lycopene and lutein degradation (R2> 0.94). Rheological analysis indicated shear-thinning behavior with consistency coefficients (K) ranging from 0.15 to 1.04 Pa.sn. Sensory evaluation reveals F2 and F8 as the most preferred formulations, with overall acceptability scores of 4.3 and 4.1 out of 5, respectively. The results demonstrate that both fiber type and carotenoid selection significantly affect antioxidant activity, stability, and sensory attributes of fortified peach nectar.